Makna Kata שָׁפַך (Shapak) Berdasarkan Kitab Kejadian 9:6 - Arlando Ridel Sumual; Farel Yosua Sualang; David Pattinama (Sekolah Tinggi Teologi Kalimantan, 2021)
Genesis 9 is the beginning of the story of God's covenant with all of His creation on earth after the flood, represented by Noah. Human life is very precious in the eyes of God, God wants people to love each other not to kill each other, through His love God made a covenant against the vengeance of shedding blood on humans. The method used is qualitative with a word study hermeneutic approach, this study aims to find the meaning of the word